Total Hip Arthroplasty: Retrospective and Comparative Study Between the Direct Anterior Approach and the Posterior Approach: Artroplastia Total da Anca: Estudo Retrospetivo e Comparativo entre a Abordagem Anterior Direta e a Abordagem Posterior - Costa, André Miguel; Fernandes, José Pedro; Silva, António Pedro; Rodrigues, Eurico Bandeira; Silva, Manuel Vieira da (Gazeta Médica, 2017)
INTRODUCTION: The constant search in total hip arthroplasty (THA) made popular minimally invasive technics like hip direct anterior approach (DAA). The aim of this study was to compare clinical and functional outcomes between DAA and posterior approach (PA) in THA. MATERIAL AND METHODS: A total of 57 patients submitted to THA by the same surgical team were selected. Criteria like position of the implant, surgery duration, hospital stay, blood loss, post-operative pain, functional recovery (WOMAC hip score) and patient satisfaction were evaluated. RESULTS: Regarding placement of the implant, the differences between both approaches were not statistically significant in all parameters (global offset, femoral-acetabular angle, leg length discrepancy). However, the DAA showed tendency for better acetabular angle results. This group had better WOMAC hip score; lower length of hospital stay, faster functional recovery and less amount of time needed to leave the crutches; nevertheless, more pain during post-operative period and increased surgery time were found. We found no significant differences in blood loss and patient satisfaction. CONCLUSIONS: Both approaches improved patients´ quality of life. These results confirm previous reports, with better implant placement, faster functional recovery and no further complications for DAA approach. A youngest patient may be the best candidate for this approach.